Awakening Transformative Learning: A Comparison of the Dissonance Experienced by Agriculture Majors During Study Abroad Courses to Costa Rica and Thailand - Janiece Pigg; Morgan A. Richardson; Richie Roberts; Kristin S. Stair (Journal of International Agricultural and Extension Education, 2020)
Students who have participated in study abroad courses exhibit an improved capacity for citizenship, emotional growth, and global competence. However, achieving such requires that study abroad courses be designed to allow students to question their underlying beliefs and values – a concept called dissonance. When individuals reflect on dissonance, it has been reported to spur a process in which their previously held perspectives are transformed. As such, this investigation sought to compare the dissonance experienced by agriculture majors (N =21) at Louisiana State University during study abroad courses to Costa Rica and Thailand. We bounded cases by academic college, degree level, and year. However, they were distinct regarding context and duration. As a result, two forms of dissonance were consistent across cases: intellectual and moral. However, within cases, we also distilled context-specific dissonance that students grappled with that helped them reconsider their previously held worldviews. Our findings demonstrated that when students processed dissonance productively, their global knowledge and perspectives were transformed. We also concluded that although shared forms of dissonance existed, it is imperative for faculty to design students’ experiences abroad purposefully to nurture students’ perspective changes in transformative ways.
Keywords: Costa Rica; dissonance; study abroad; Thailand; university agriculture students